Studi Analisis Etika Komunikasi dalam Kebebasan Berekspresi Pada Penulisan Smut Fan Fiction - Jasmine Alya Pramesthi (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2026)
Freedom of opinion is a form of channeling the expression of each individual in cyberspace or the internet. One form of self-expression and creativity is writing. There are various social media that support each individual in expressing creativity in terms of writing, including blogging or writing fiction. Various types of stories are presented in fan fiction writing, one of which is the type of love story that leads to the context of sexuality. The Korean Wave is one factor in the growing popularity of fan fiction writing. There are more than hundreds of thousands of fan fiction that have been produced about BTS, 570 thousand of which are fan fiction with mature material. This research was conducted using a qualitative approach and descriptive method. The following study uses primary data collected based on fanfiction content uploaded on the Wattpad website which is then analyzed using various literature and previous studies on communication ethics, freedom of opinion, and fanfiction writing. In the following study, researchers attempted to criticize cases that occurred in the fandom, which could give their idol a loss. This study explains that there are still violations of communication ethics committed by some fans to their idols through writing fan fiction. This is considered to violate communication ethics because of the uncomfortable feelings expressed by the object, namely his idol. Researchers formulate suggestions for future researchers to conduct a more in-depth analysis of both those who are contra and those who agree with the practice of writing fanfiction that leads to sexual behavior to provide broader insight into the following two perspectives.